EXPLORING IMPULSIVE BUYING OF ESPORT PLAYER AMONG SAM RATULANGI UNIVERSITY STUDENTS - Morissa Wongkar; Paulus Kindangen; Emilia Gunawan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The purpose of this research is to analyze the influence of external and internal trigger of impulsive buying on esport player undergraduate student at the Sam RatulangiUniversity and also to find out the consequences of it.  The method that used in this research is qualitative method with 15 informants as the respondents for the research distributed by social media. The result of this research shows that internal trigger has the most influencing for esport player to make impulsive buying and also for some of esport player feel the consequences after make impulsive buying such as the feeling or regret. Description qualitative were used to help the data analysis in this research.